Perancangan Website Interaktif dengan Pendekatan Visual Branding untuk Meningkatkan Citra Luthfia House Cake - Aulia Rahma Dira Nasution; Dea Ramadhani; Qistina Alia Athira; Sularno .; Novadilastri . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving economic growth through product innovation and the utilization of digital technology. This report aims to describe the profile, history, and products and services offered by Luthfia House Cake, an MSME operating in the Food and Beverage (F&B) sector in Padang City. The study employed a descriptive qualitative method by collecting data through observation and documentation. The findings indicate that Luthfia House Cake was established in 2022 and implements a pre-order system to maintain product quality and production efficiency. Its main products are customized birthday cakes designed according to customers’ preferences and requirements. In its marketing activities, the business utilizes social media, particularly Instagram and WhatsApp Business, as platforms for promotion and communication with customers. This strategy has helped increase customer trust, expand market reach, and foster customer loyalty. Although the business still faces challenges in maintaining consistent digital promotional content, Luthfia House Cake continues to develop product innovations, improve service quality, and strengthen its brand identity. Therefore, Luthfia House Cake demonstrates that the implementation of digital marketing strategies, high product quality, and excellent customer service are essential factors in supporting the growth and competitiveness of MSMEs in the digital era.